How the Immune System Deploys Creativity: Why We Can Learn From Astronauts and Cosmonauts - de Vries, Henderika; Khoury-Hanold, William (Frontiers in Psychology, 2021)
In this interdisciplinary paper, we investigate the relationship between creativity and the immune system; the creative features of the immune system and how the immune system and its role in regulating homeostasis might be related to creative cognition. We argue that within a multivariate approach of creativity, the immune system is a contributing factor. New directions for research are also discussed. When astronauts and cosmonauts venture into the new and extreme environment of outer space, their immune system needs to instantly adapt and find new answers to survive biologically and psychologically. Many astronauts report interest in creative activities and therefore represent an interesting group to investigate creativity in relation with the immune system. Little is known regarding 1) how the immune system interacts with and supports creative cognition and behavior, 2) if an individual’s immune system, interacting with cognition, adapts more originally to a new environment compared to another’s; in other words, if there is creativity in the domain of the immune system, and 3) the creative properties and functions of the immune system itself.